Patterns of breast reconstruction in patients diagnosed with inflammatory breast cancer: The Dana‐Farber Cancer Institute's Inflammatory Breast Cancer Program experience. Issue 3 (25th August 2019) - Nakhlis, Faina; Regan, Meredith M.; Chun, Yoon S.; Dominici, Laura S.; Caterson, Stephanie; Bellon, Jennifer R.; Warren, Laura; Yeh, Eren D.; Jacene, Heather A.; King, Tari A.; Overmoyer, Beth
Abstract: Inflammatory breast cancer (IBC) exhibits dermal lymphatic involvement at presentation, and thus, the standard surgical approach is a nonskin‐sparing modified radical mastectomy (MRM) without breast reconstruction (BR). In this study, we evaluated immediate and delayed BR receipt and its outcomes in IBC. Using an IRB‐approved database, we retrospectively evaluated stage III IBC patients who received trimodality therapy (preoperative systemic therapy, followed by MRM and postmastectomy chest wall/regional nodal radiation). Patients with an insufficient response to preoperative systemic therapy and/or who required preoperative radiotherapy were excluded. BR receipt, timing, and morbidity were evaluated. Among 240 stage III IBC patients diagnosed between 1997 and 2016, 40 (17%) underwent BR. Thirteen (33%) had immediate, and 27 (67%) had delayed BR. Four patients had complications (1 [8%] immediate BR and 3 [11%] delayed BR); only 1 BR (delayed) was unsuccessful. From the MRM date, the median time to recurrence was 35 months (<1‐212) and median overall survival was 87 months (<1‐212). In this cohort of stage III IBC patients, only 11% pursued delayed BR following trimodality therapy, possibly attributable to the observed high recurrence rates hindering BR. Further studies addressing BR outcomes in IBC are needed for better counseling patients regarding their reconstructive options.